2015
DOI: 10.1186/s12891-015-0562-x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity at work and quality of life in patients with rheumatoid arthritis

Abstract: BackgroundThe aim of this study was to determine which combination of personal, disease-related and environmental factors is best associated with at-work productivity loss in patients with rheumatoid arthritis (RA), and to determine whether at-work productivity loss is associated with the quality of life for these patients.MethodsThis study is based on cross-sectional data. Patients completed a questionnaire with personal, disease-related and environmental factors (related to the work environment), and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 39 publications
2
40
2
5
Order By: Relevance
“…30 The studies by van Vilsteren et al concluded that patients suffering from RA with low quality of life are characterized by decreased productivity. 26 Our study showed that economic activity has a positive effect on the general health level according to GHQ-30. Factors such as higher education and living in a city also had a positive effect on general health (GHQ-30).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…30 The studies by van Vilsteren et al concluded that patients suffering from RA with low quality of life are characterized by decreased productivity. 26 Our study showed that economic activity has a positive effect on the general health level according to GHQ-30. Factors such as higher education and living in a city also had a positive effect on general health (GHQ-30).…”
Section: Discussionmentioning
confidence: 52%
“…21,23,24 It was also shown that the quality of life of patients with RA depends on many factors of physical, mental and social functioning sphere. 17,[19][20][21][23][24][25][26][27][28][29][30][31] Studies conducted by many authors have shown that poorer functioning of the respondents in the physical sphere is conditioned by the duration of the disease. 18,24,26,28,30 Studies by Baloglu et al and Wisłowska et al did not confirm this dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly this aspect has been studied in RA 12,13,14 . In economic analyses, costs can be considered in different categories.…”
Section: Rheumatologymentioning
confidence: 99%
“…2 Penyakit ini sering menyebabkan kerusakan sendi, kecacatan dan banyak mengenai penduduk pada usia produktif, sehingga memberi dampak sosial dan ekonomi yang besar. [3][4][5][6] Para klinisi seringkali menganggap bahwa dampak terpenting dari AR ialah nyeri dan kehilangan fungsi akibat dari sinovitis dan kerusakan sendi. Tetapi artritis reumatoid memengaruhi kehidupan penderitanya melebihi aspek-aspek yang secara tradisional dikenal sebagai aspek medis.…”
Section: Pendahuluanunclassified
“…Dampak besar bagi penderita ialah hendaya yang diakibatkan hilangnya fungsi anatomi atau fisiologi, sehingga menyebabkan gangguan, keterbatasan atau bahkan ketidakmampuan untuk melakukan perannya sebagai individu dalam kehidupan. 5,6 H i n g g a awal abad ke-20, paradigma dalam pengobatan atau pengelolaan pasien ialah hilang atau tidak adanya penyakit (absence of illness). Hal ini terutama dikarenakan pada masa itu penyakit yang mendominasi ialah penyakit infeksi (menular).…”
Section: Pendahuluanunclassified